НОВЫЕ ДАННЫЕ ПО СТРАТИГРАФИИ ВЕНЛОКСКИХ ОТЛОЖЕНИЙ БОЛЬШЕЗЕМЕЛЬСКОЙ ТУНДРЫ - Антошкина А.И.; Безносова Т.М. (My University, 1988)
The Bezymyannaya Suile is distinguished in Silurian deposits of the Padimeityvis River. The study of brachiopods. corals and stromatoporoids has shown that the suite belongs to the Upper Wenlock.
Keywords: Венлокский; 551.733.2.(470.1); Палеозой::Силурийская::Венлокский